Republic of Slovenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper takes the case of Slovenia to analyze credit growth and economic recovery in Europe. The findings reveal that following the global financial crisis recovery in Slovenia significantly lags typical postrecession recoveries for both typical and financial-crisis-driven recessions. Credit dynamics have also been much more subdued. Controlling for Slovenia's double-dip recession and the slowdown in global growth after the global financial crisis reveals that Slovenia's recovery is not atypical. The cross-country study also finds that bank-specific factors are the key determinants of bank lending. Bank credit to the private sector also has a positive but modest impact on economic activity, mainly through the investment channel.